Pedestrian accident analysis measuring accident potential at intersections - Ares, Lilibeth E. (1998)
Road safety researches have been, for the most part, neglected in the Philippines. This, in spite of the fact that road traffic accident statistics show that accident frequencies have been following an increasing trend. In particular, pedestrian safety should be given focus since pedestrian-vehicle accidents account for most of the total fatal and injury accidents that occur. Current methods of studying accident causation are limited to the analysis of the attendant circumstances accompanying traffic accidents. However, this method, although yielding relevant results, is much to dependent on the existence of a comprehensive accident database. As such, the development of alternative methods of analysis is recommended especially for the Philippines where the collection and storage of traffic accident data is in disorder. This study seeks to initiate an application of a technique called the Traffic Conflict Technique in the identification of factors contributing to pedestrian accidents. This technique was developed primarily as an aid in analyzing causes of accidents by observing conflicts between two road users (vehicle-vehicle or vehicle-pedestrian) with the basic assumption that conflicts are actually accidents minus the final component (collision). In the study, two high accident intersections were observed for pedestrian-vehicle conflicts in an attempt to describe the existing hazardous conditions at the intersections. For purposes of simplifying this initial investigation, only conflicts between pedestrians and through vehicle movements were observed. Results of the surveys conducted reveal that the leading causes of pedestrian-vehicle conflicts are (a) presence of pedestrians at roadsides, and (b) pedestrian crossing violations. Generally, the situation seems to be induced by the lack of proper and adequate pedestrian facilities at the intersection, as well as the negligence of the concerned authorities in implementing rules and regulations. To this end, the study recommends countermeasures that revolve around the three E's of transportation: engineering, education, and enforcement. In addition, the study also made an effort to start a traffic accident database in Quezon City using GIS technology. It is expected that this would serve as an impetus to starting a nationwide comprehensive accident database.